Una supuesta edición (post)incunable desenmascarada: análisis tipográfico y motivaciones procesales de la impresión de los Privilegios colombinos capitulados en Santa Fe - Mercedes Fernández Valladares (Janus: Estudios sobre el Siglo de Oro)
From typographical, documentary and historical points of departure, this article deals with a printed pamphlet in the archives of the House of Alba which contains the transcription of the letter confirming the privileges accorded to Christopher Columbus by the Catholic Monarchs in the Capitulations of Santa Fe. Whilst the text and the historical event that it derives from are both well known, here for the first time the attempt is made to identify the typography of this document, which hitherto has only rarely been referred to. As a result, its status as an incunable or post-incunable is rejected and its publication is related to the progress of the so-called Columbus lawsuits, which were to play such an important role in the history and development of legal proceedings.